The Effect of Stunting on Child Growth and Development - Akbar, Resti Rahmadika; Kartika, Windy; Khairunnisa, Mutiara (CV. AKBAR PUTRA MANDIRI, 2023)
Stunting is one of the leading public health problems in lower-middle-income countries, including Indonesia. Stunting is a problem of chronic malnutrition caused by insufficient nutritional intake over a long period due to food that does not meet the dietary needs required. Nutritional issues in young children can have serious consequences; according to the World Health Organization, stunting can cause cognitive or intelligence, motor, and verbal development to develop sub-optimally, increase the risk of obesity and other degenerative diseases, increase health costs, and increase the incidence of morbidity and death. This literature review aims to determine the effect of stunting on children's growth and development and the influencing factors. Search for keywords: Stunting, growth, and development of checking in children, children, cognitive and motor skills. The conclusion from the literature review is that there is a significant relationship between stunting influence on motoric development in children, and the factors that cause stunting do not only come from the child but many external factors that influence such as maternal, economic, environmental, and infectious diseases factors and not only that. Feeding patterns are also one of the factors causing stunting in children.